Analisis Pelaporan Keuangan Segmentasi Pada PT Unilever Tbk dan Entitas Anak Tahun 2021-2022 (International Forum of Researchers and Lecturers, 2024)
Financial reporting is a crucial tool for public companies in aiding internal decision-making regarding the development of business activities. To provide meaningful value, financial statements must be presented and accounted for accurately. According to IFRS and SAK, consolidated financial statements represent the assets, liabilities, equity, revenue, expenses, and cash flows of the parent and subsidiary entities as a single economic entity.Segment reporting, now referred to as operating segments, encompasses components of an entity engaged in business activities, regularly evaluated for resource allocation decision-making and performance assessment. This research focuses on the segment reporting disclosure at PT Unilever Tbk and its subsidiaries. Through the ten percent revenue test, ten percent profit or loss test, and ten percent asset test, it was found that segments related to household, personal care, and food and beverages meet the segment reporting criteria.The results of this analysis provide a deeper understanding of the financial statements of PT Unilever Tbk and its subsidiaries, supporting the conclusion that these segments meet the segment reporting requirements under PSAK No. 5.